Особенности электронной структуры систем ZR-HE, ZR-H, ZR-HE-H - Лопатина О. В. Оксана Валерьевна; Святкин Л. А. Леонид Александрович; Коротеев Ю. М. Юрий Михайлович; Чернов И. П. Иван Петрович (2015, 2015)
Заглавие с экрана